Program to Promote Positive Parenthood at School: A Preliminary Study in a Socially Vulnerable Context - Vargas Rubilar, Jael Alejandra; Richaud, María Cristina; Oros, Laura Beatriz (Pensando Psicología, 2018)
Introduction: Positive parenting requires the balanced combination of various essential factors, such as attachment, affection, communication, discipline and autonomy granted to children.Objective: This study explored the impact of a parental strengthening program based on the assessment of participating mothers and their children.Method: The program was implemented in groups through expository-participative meetings at a school in a socially vulnerable context. After its application, semi-structured interviews with the mothers were conducted; in addition, the attachment and parental style perceived by their respective children before and after the program were evaluated and compared with a control group.Results: We found that the workshops, as reported by the participants, provided novel information that contributed to their personal growth and parental sensitivity; produced a change in beliefs regarding parenting and an improvement in the expression of affection, verbal communication and discipline; was an important source of social support; and activated their interest in the school situation of their children, which improved—in some cases—communication between mothers and the school. Moreover, the children’sperception of attachment and parenting style was better after the intervention with the mothers and better than that observed in the control group.Conclusions: It is concluded that the intervention program had a favorable impact on different maternal aspects that encourage the exercise of positive parenthood.
Keywords: intervention; effectiveness/impact; positive parenthood; social vulnerability